Evaluating the implementation of the Inverse Care Law Programme in Wales, a population based intervention in primary care. (2018) - Akbari, Ashley; Song, Jiao; Cox, Caryn; May, Leon; Watkins, Williams; Thomas, Sarah; Aitken, Sarah; King, William
No abstract available